2015
DOI: 10.1186/s40035-015-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

New developments and future opportunities in biomarkers for amyotrophic lateral sclerosis

Abstract: Modern technology has improved the ability to probe effectively the underlying biology of ALS by examination of genomic, proteomic and physiological changes in patients with ALS, as well as to monitor functional and structural changes during the course of disease. While effective treatments for ALS are lacking, the discovery of sensitive biomarkers to disease activity offers clinicians tools for rapid diagnosis and insights into the pathophysiology of ALS. The ultimate aim is to lessen reliance on clinical mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 109 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…These advanced techniques are surface and voxel based morphometry. The first is known as "cortical thickness measure" because it allows decomposition of cortical volume into both thickness and surface area and respects cortical topology [18]. The second, voxel base morphometry, allows the regional assessment of grey-matter (GM) and white matter density (WM) [5].…”
Section: Structural Mrimentioning
confidence: 99%
See 4 more Smart Citations
“…These advanced techniques are surface and voxel based morphometry. The first is known as "cortical thickness measure" because it allows decomposition of cortical volume into both thickness and surface area and respects cortical topology [18]. The second, voxel base morphometry, allows the regional assessment of grey-matter (GM) and white matter density (WM) [5].…”
Section: Structural Mrimentioning
confidence: 99%
“…Post-mortem histopathological studies have demonstrated widespread cerebral white matter tract damage in ALS and this alteration can now be detected non-invasively using diffusion tensor imaging [18].…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%
See 3 more Smart Citations